RITUAL MATTAMPUNG: MENALAR GAP DI KALANGAN MASYARAKAT SOPPENG RIAJA DI BARRU SULAWESI SELATAN - Nasruddin (STAIN MAJENE, 2022)
The mattampung ritual is a practice of beliefs and traditions carried out by the Bugis in order to remember the spirits of the deceased by reciting prayers or verses of the Qur'an in order to gain salvation and get the right place by the side of Allah. The purpose of this study is to reveal an understanding of the ritual of mattampung among the people. This type of research is qualitative usingnormative theological proximity which is then supported by an interview with a local scholar. The results of this study revealed that the rituals of mattampung can be studied based on legal sources. The first source of law based on naqly's postulates is the Qur'an and hadith. While the second source of law is the aqly postulate which is the source of law based on reason. later, developed by the scholars of ushul fiqhi on the basis of ijtihad. The difference in people's understanding of the death ritual in Soppeng Riaja District, Barru Regency, is because on the one hand that the ritual is an Islamic culture by relying on two postulates, namely the naqli postulate (al-Qur'an and Hadith) and also the aqli (reason consideration) postulate which is used by ushul fiqhi scholars as one of the sources of Islamic law, namely al- Urf' (the establishment of laws based on customs and traditions carried out by the local people).